Nostalgia franquista y propaganda gráfica contra la Transición: el tebeo El General más joven de Europa, de Heraldo Español - David Gregorio (Cahiers de Civilisation Espagnole Contemporaine)
Heraldo Español, a far-right weekly that existed between 1980 and 1982 and edited by Julio Merino, published a biographical comic in its early months, with texts by Merino himself. Entitled Franco, el general más joven de Europa, the 14 parts of this comic retraced Franco's career from the Moroccan war until he became a general. The stated aim was to teach children to admire the future dictator, by insisting in his charismatic qualities, but also to criticism the second period of the Transition. To do this, the comic strip set his story in a classroom in 1980, with the lessons of Don Antonio, a very special teacher who, in front of a few children, gave a partial and propagandist history lesson. Aligned with the editorial line of Heraldo Español, this comic sought to fuel nostalgia for Francoism while attacking the new democratic regime.